Efektivitas Pemberian Berbagai Dosis Pupuk Cair Urine Sapi terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris L.) pada Lahan Podsolik - Nur Hafizah; Syahran Syahran (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2015)
Beans (Phaseolus vulgaris L.) are loaded with vitamin A, B and Can important source of vegetable. Problems faced in the development of crop farming on the land podzolic very low pH and nutrient poor. This study aims to (i) determine the effect of cow urine liquid fertilizer on the land podsolic on growt hand yield of beans, (ii) get adose of liquid fertilizer of cow urine is best for the growt hand yield of chick peain podzolic land. The research was conducted in Pantai Hambawang Timur Village Labuan Amas Selatan District Hulu Sungai Tengah Regency, June-July 2014, this study uses randomized block design (RBD), with 5 treatments and 4 replications, so we get 20 units of the experiment, and each treatment there 4 plants. The factors tested are liquid fertilizer of cow urine, namely: t0 = 0 cc.ℓ-1 per map, t1 = 35 cc.ℓ-1 per map, t2 = 45 cc.ℓ-1 per map, t3 = 55 cc. ℓ-1 per map, t4 = 65 cc.ℓ-1 per map. The results of this study indicate. That treatment doses of liquid fertilizer of cow urine significantly affect thelength of the plant ages 15, 25 and 35 DAP, number of pods and pod weight of cropat a dose of 65 cc perlite r of water perplot (t4). So the bean plants can be grown on land podzolic when treated with optimal doses of liquid fertilizer of cow urine according to his research, by using a dose of 65 cc.ℓ-1 per map